(untitled) (Journal of Informatics Education and Research, 2025)
The recent developments in the field of sustainable entrepreneurship increasingly acknowledge the transformative possibilities of digital technologies to neutralize the impact of societal and environmental challenges via innovative entrepreneurial mind set. However, as of now, the empirical research in the domain of digital sustainable entrepreneurship is dispersed and disjointed lacking the consolidation to move forward. This conceptual research aims to contribute to the field of sustainable entrepreneurship and business model research by discovering the role of digital technologies in creating socio-environmental value driven business models. This research explores the factors which work in cohesion and those which propose a potential challenge for the amalgamation of sustainability and digital technology. The intention is to achieve a deeper understanding of how to achieve sustainable development from an entrepreneur point of view. This research throws light on the components of sustainable business models having digital technologies at its core. Practical implications for sustainable entrepreneurs have also been discussed.